The Capacity of the Fecal Microbiota From Malawian Infants to Ferment Resistant Starch - Wang, Yanan; Mortimer, Elissa K.; Katundu, Kondwani G. H.; Kalanga, Noel; Leong, Lex E. X.; Gopalsamy, Geetha L.; Christophersen, Claus T.; Richard, Alyson C.; Shivasami, Aravind; Abell, Guy C. J.; Young, Graeme P.; Rogers, Geraint B. (Frontiers in Microbiology, 2019)
In Low and Middle-Income Countries (LMIC), weaning is associated with environmentally- acquired and inflammation-associated enteric disorders. Dietary intake of high amylose maize starch (HAMS) can promote commensal fermentative bacteria and drive the production of short chain fatty acids (SCFAs). By stabilising commensal gut microbiology, and stimulating the production of anti-inflammatory metabolites, HAMS supplementation might therefore infant enteric health. However, the extent to which the gut microbiota of LMIC infants are capable of fermenting HAMS is unclear. We assessed the capacity of the faecal microbiota from pre-weaning and weaning Malawian infants to ferment HAMS and produce SCFAs using an in vitro fermentation model. Faecal microbiota from both pre-weaning and weaning infants were able to ferment HAMS, as indicated by an increase in bacterial load and total SCFA concentration, and a reduction in pH. All of these changes were more substantial in the weaning group. Acetate production was observed with both pre-weaning and weaning groups, while propionate production was only observed in the weaning group. HAMS fermentation resulted in significant alterations to the faecal microbial community in the weaning group, with significant increases in levels of Prevotella, Veillonella and Collinsella associated with propionate production. In conclusion, faecal microbiota from Malawian infants before and during weaning has the capacity to produce acetate through HAMS fermentation, with propionate biosynthetic capability appearing only at weaning. Our results suggest that HAMS supplementation might provide benefit to infants during weaning.